PENGARUH PELATIHAN HOLLOW SPRINT TERHADAP KECEPATAN DAN KAPASITAS VITAL PARU - Anom Jinawi, Dewa Nyoman (Universitas Pendidikan Ganesha, 2013)
This study aimed to determine the influence of hollow sprint trining toward speed and lungs vital capacity. It was a quasi experiment study with nonrandomized pretest posttes control groups design. The subjects of this researh were 30 male students of SMA N 1 Sidemen who were joining basketball extracuriculer. Data of speed was collected through 60 meters sprint and lungs vital capacity data was collected through spirometer. All of the collected data were analyzed with independent t-test in which the significancy was (α) 0,05 with assistance of SPSS 16,0. The result of data analysis by using independent t-test showed that hollow sprint influenced the improvement of speed and lungs vital capacity with significance 0,000 and 0,000, repectively. Based on the reseach finding, it can be concluded that hollow sprint has an influence toward speed improvement and lungs vital capacity. It is suggested to sports practitioners (supervisor, coach, sport teacher, and athletes) to use hollow sprint as one of alternatives in increasing velocity and lungs vital capacity.